Environmental management accounting practices in small medium manufacturing firms - Muhammad Jamil, Che Zuriana; Mohamed, Rapiah; Muhammad, Faidzulaini; Ali, Amin (Elsevier Ltd., 2015)
This study investigates factors and barriers which influence the practice of environmental management accounting (hereafter known as EMA).The institutional theory is employed and data is collected via questionnaire.This study focuses on small medium enterprises (hereafter known as SMEs) specifically, Malaysian small medium manufacturing firms.The results indicate that most firms have a budget allocation for environmental activities and practice physical EMA.The study argues that coercion is a dominant factor for practicing EMA and therefore, barriers to EMA development should be resolved by the Malaysian government and other authorities.